Kontakte: Für elektronische klänge, klavier und schlagzeug - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2009)
6 DVDs:Stockhausen rehearses KONTAKTE for electronic sounds, piano and percussion on November 26th1997 with Christian Nagel ( piano ) and Michael Pattmann ( percussion ) at the Folkwang Hochschule inEssen ( Archive Nos. 105 / 2 to 105 / 6 ) and performance on November 27th 1997 ( Archive No. 205 / 7 )( Colour films by Suzanne Stephens )rehearsals of KONTAKTE on Nov. 26th 1997 and concert on Nov. 27th 1997.